Increased prevalence of pathogenic bacteria in the gut microbiota of infants at risk of developing celiac disease: The PROFICEL study. (2nd November 2018) - Olivares, Marta; Benítez-Páez, Alfonso; de Palma, Giada; Capilla, Amalia; Nova, Esther; Castillejo, Gemma; Varea, Vicente; Marcos, Ascensión; Garrote, José Antonio; Polanco, Isabel; Donat, Ester; Ribes-Koninckx, Carmen; et al.
ABSTRACT: Celiac disease (CD) is an immune-mediated enteropathy involving genetic and environmental factors, whose interaction influences disease risk. The intestinal microbiota, including viruses and bacteria, could play a role in the pathological process leading to gluten intolerance. In this study, we investigated the prevalence of pathogens in the intestinal microbiota of infants at familial risk of developing CD. We included 127 full-term newborns with at least one first-degree relative with CD. Infants were classified according to milk-feeding practice (breastfeeding or formula feeding) and HLA-DQ genotype (low, intermediate or high genetic risk). The prevalence of pathogenic bacteria and viruses was assessed in the faeces of the infants at 7 days, 1 month and 4 months of age. The prevalence of Clostridium perfringens was higher in formula-fed infants than in breast-fed over the study period, and that of C. difficile at 4 months. Among breastfed infants, a higher prevalence of enterotoxigenic E. coli (ETEC) was found in infants with the highest genetic risk compared either to those with a low or intermediate risk. Among formula-fed infants, a higher prevalence of ETEC was also found in infants with a high genetic risk compared to those of intermediate risk. Our results show that specific factors, such as formula feeding and the HLA-DQ2 genotype, previously linked to a higher risk of developing CD, influence the presence of pathogenic bacteria differently in the intestinal microbiota in early life. Further studies are warranted to establish whether these associations are related to CD onset later in life.